2016
DOI: 10.1038/srep39306
|View full text |Cite
|
Sign up to set email alerts
|

Real-time detection of dielectric anisotropy or isotropy in unconventional oil-gas reservoir rocks supported by the oblique-incidence reflectivity difference technique

Abstract: Current geological extraction theory and techniques are very limited to adequately characterize the unconventional oil-gas reservoirs because of the considerable complexity of the geological structures. Optical measurement has the advantages of non-interference with the earth magnetic fields, and is often useful in detecting various physical properties. One key parameter that can be detected using optical methods is the dielectric permittivity, which reflects the mineral and organic properties. Here we reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…High-resolution fractures can also be identified by SEM imaging analysis 56 . Thin sections, which were impregnated with blue epiflourescent epoxy, were analyzed under plane-polarized and cross-polarized light to determine intergranular and intragranular pores at Houston Advanced Technology Center of Core Laboratory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-resolution fractures can also be identified by SEM imaging analysis 56 . Thin sections, which were impregnated with blue epiflourescent epoxy, were analyzed under plane-polarized and cross-polarized light to determine intergranular and intragranular pores at Houston Advanced Technology Center of Core Laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…Scanning electron microscope (SEM) analysis was conducted on the fresh surfaces of the core plug samples which are coated with gold to help detect the micropores associated with authigenic clay minerals. High-resolution fractures can also be identified by SEM imaging analysis 56 . Thin sections, which were impregnated with blue epiflourescent epoxy, were analyzed under plane-polarized and cross-polarized light to determine intergranular and intragranular pores at Houston Advanced Technology Center of Core Laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…The shale sample used in the LIV measurement was cored in the horizontal direction with a cylindrical plug from a whole specimen of a shale formation at the depth of 3325.4 m. The diameter and height of the core was 25 and 60 mm, respectively. Optical microscopy images and SEM pictures of the core sample used here were shown in our previous study [25], in which the orientational arrangement of the particles and crevices could be observed by the SE morphology contrast and BSE images. Besides, the layered distribution of the dielectric properties in the shale sample were also identified, and the width of the adjacent main beddings was measured as ~100-300 μm, as well as the secondary laminations ~30-50 μm.…”
Section: Experimental Methodsmentioning
confidence: 55%
“…Optical methods, which are insensitive to harsh physical environment, can be served as an appropriate method to promote the development of unconventional oil-gas industry. In our previous study [25], the anisotropy of shale was clearly observed in the OIRD images, and such method is proved promising in surface anisotropy detection in rock. Here in this work, LIV is employed to study the electrical anisotropy of shale, and periodic variation of V p was observed with the angle.…”
Section: V90mentioning
confidence: 88%
See 1 more Smart Citation